Wnt Acts as a Prosurvival Signal to Enhance Dentin Regeneration. (July 2015) - Hunter, Daniel J; Bardet, Claire; Mouraret, Sylvain; Liu, Bo; Singh, Gurpreet; Sadoine, Jérémy; Dhamdhere, Girija; Smith, Andrew; Tran, Xuan Vinh; Joy, Adrienne; Rooker, Scott; Suzuki, Shigeki; et al.
Abstract Wnt proteins are lipid‐modified, short‐range signals that control stem cell self‐renewal and tissue regeneration. We identified a population of Wnt responsive cells in the pulp cavity, characterized their function, and then created a pulp injury. The repair response was evaluated over time using molecular, cellular, and quantitative assays. We tested how healing was impacted by wound environments in which Wnt signaling was amplified. We found that a Wnt‐amplified environment was associated with superior pulp healing. Although cell death was still rampant, the number of cells undergoing apoptosis was significantly reduced. This resulted in significantly better survival of injured pulp cells, and resulted in the formation of more tertiary dentin. We engineered a liposome‐reconstituted form of WNT3A then tested whether this biomimetic compound could activate cells in the injured tooth pulp and stimulate dentin regeneration. Pulp cells responded to the elevated Wnt stimulus by differentiating into secretory odontoblasts. Thus, transiently amplifying the body's natural Wnt response resulted in improved pulp vitality. These data have direct clinical implications for treating dental caries, the most prevalent disease affecting mankind. © 2015 American Society for Bone and Mineral Research.